Examining corporate social responsibility awareness: An unaided recall measure. Issue 5 (12th January 2021) - Rayne, Daniel; Pervan, Simon; McDonald, Heath; Leckie, Civilai
Abstract: As professional sports teams commonly partner with multiple charity organizations to achieve corporate social responsibility objectives, the purpose of this research was to measure charity brand awareness among sports fans via unaided recall. Further, this study proposed antecedents to awareness, including; level of fandom, overall season‐ticket holder (STH) satisfaction, perceptions of on‐field performance, live game viewership frequency, televised game viewership frequency, and digital channel interaction frequency. A survey was used to collect data from STHs across three professional sports teams ( n = 8, 414). Fan recall of charity partners was low with 1.3% recalling three, 3.5% recalling two, and 9.6% able to recall at least one charity partner. Of the antecedents, overall STH satisfaction and frequency of live game viewership were the most influential while, perceptions of on‐field performance returned a significant and negative result. It is advocated sports teams reduce the number of charity partners and charity managers focus communication efforts on more contented STHs who attend live games regularly.